MicroRNAs Expression Profile in Young Patients with Acute Myocardial Infarction - Muhammad Musa, Nurul Ashikin; Abdullah, Nor Zamzila; A. Talib, Norlelawati; Mohd Shah, Azarisman Shah; Abdullah, Aszrin; Mohd Shah, Aida Nur Sharini (IIUM Medical Journal Malaysia, 2022)
Introduction: Acute myocardial infarction (AMI) is a severe coronary heart disease. Targeted miRNAs studies implicated two main pathways in the regulation of AMI namely pro-apoptosis (miR-29b and miR-194-5p on PTEN) and pro-necroptosis (miR-325 & miR-105 on RIPK3 ) pathways. This study aims to profile the miRNAs in Healthy Controls, Young AMI, and Mature AMI patients with matching criteria. MATERIALS AND Methods: Total RNA was extracted from plasma and the miRNA expression profiling using small RNA was done on the BGISEQ500 SE5 sequencing platform with BGI sequencing libraries. The sequence data were analysed using Gene Ontology (GO) to determine the function of the differently expressed genes, while Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analyses were applied to identify the biological pathways in Young AMI against Mature AMI. Results: Of 1497 differentially expressed miRNAs, 1090 miRNAs were upregulated, and 407 miRNAs were downregulated in Young AMI against Mature AMI. The top 10 upregulated miRNAs were miR-552, miR-4446-3p, miR-432-5p, miR-548j-5p, miR-219, miR-982, miR-181a-2-3p, miR-654-5p, miR-58 and miR-548k; while the top 10 downregulated were miR-16-5p, miR-1064, miR-431-5p, miR-790 miR-1177, miR-201, miR-105, miR-518, miR-419 and miR-1103. There were 9 novel miRNAs discovered in this study; miR-58, miR-982, miR-548k, miR-1064, miR-790, miR-1177, miR-201, miR-419, and miR-1103. The target genes of differentially expressed miRNAs that were mapped to the signal transduction pathway in KEGG indicated that 346 classes were enriched. Conclusion: Our miRNA profiling revealed differentially expressed miRNAs including 9 novel miRNAs in Young and Mature AMI that require further evaluations for their roles in AMI.